Pembangunan Minda Ummah Berasaskan Asas Utama Pemikiran Epistemologi Islam: Satu Perbincangan - Hamat, Mohd Fauzi (Jurnal Usuluddin, 2002)
This articles tries to elaborate the developing of Muslim mind based on Islamic epistemological thoughts especially which is concerns with the development of Malay mind in this country. The discussion will touch the important of better understanding the concept of ’certain knowledge’ (’Ilm al-Yaqin) in Islamic tradition and the methodology of achieving that kind of exclusive knowledge in relation to the development of Muslims mind. Some suggestions are raised to solve the problems of Malay weakness in thinking nowadays.